The nature of the rainfall onset over central South America - González, Marcela Hebe (2007)
The objective of this work is to provide a detailed description of the onset of the South American Monsoon based on precipitation observations available over tropical and subtropical South America. The analysis was also performed using outgoing longwave radiation (OLR) data in order to assess the ability of this particular dataset to reproduce the main features associated with precipitation evolution during austral spring. Results show that both OLR and precipitation data agree in describing the progression of convection from the northwest and southeast into central Brazil by the beginning of October. Moreover the assessment of available methods to identify onset dates shows that the method of Kousky (1988), based on the OLR evolution, provides the onset date in most of South America, without regionally adaptation, as the methods based on rainfall generally require. Composite fields show that rainfall in central Brazil begins with moderate rates, which are still lower than those observed over the northwestern and southeastern tropical regions. After the rainfall jump, that on average occurs three pentads later than the onset of rainfall, precipitation rates increase over central Brazil and similar rates are observed over the entire tropical region. It is suggested that transient activity, which occurs around the onset period when the atmospheric mean conditions are getting more unstable as they approach summer-like conditions, is the one that imprints a rainfall-jump feature in the precipitation evolution. The character of changes in the precipitation rate, as the rainy season develops, provides complementary information that can be used together with onset date.